2013
DOI: 10.3892/mmr.2013.1803
|View full text |Cite
|
Sign up to set email alerts
|

Basic fibroblast growth factor increases the transplantation-mediated therapeutic effect of bone mesenchymal stem cells following traumatic brain injury

Abstract: Basic fibroblast growth factor (bFGF) has proven useful for neural stem and progenitor cells during the transplantation‑mediated therapeutic effect of bone mesenchymal stem cells (BMSCs). Endogenous bFGF expression levels increase during brain development and gradually diminish with aging. To date, few studies have been conducted on exogenous bFGF promoting BMSC transplantation‑mediated functional recovery in adult rats following traumatic brain injury (TBI). The results of the present study showed that BMSCs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 27 publications
0
12
0
4
Order By: Relevance
“…21 24 Nevertheless, by delivering FGF-2 with bone marrow derived MSCs by stereotactic injection, Bhang and colleagues 28 found increased expression of neuronal and astrocytic markers and improvement in animal motor function. Liu and colleagues 36 directly injected FGF-2 into the lateral ventricle and showed a higher survival rate in transplanted bone marrow derived MSCs and increased differentiation into neuronal and glial cells, but no functional recovery.…”
Section: Mesenchymal Stem Cellsmentioning
confidence: 99%
“…21 24 Nevertheless, by delivering FGF-2 with bone marrow derived MSCs by stereotactic injection, Bhang and colleagues 28 found increased expression of neuronal and astrocytic markers and improvement in animal motor function. Liu and colleagues 36 directly injected FGF-2 into the lateral ventricle and showed a higher survival rate in transplanted bone marrow derived MSCs and increased differentiation into neuronal and glial cells, but no functional recovery.…”
Section: Mesenchymal Stem Cellsmentioning
confidence: 99%
“…As a result, it is imperative to deliver the growth factors into the brain near the injury. Liu et al showed that intracerebroventricular administration of fibroblast growth factor 2 (FGF2) for 7 days beginning at the time of MSC transplantation resulted in faster improvement in the forelimb placing and balance beam tests compared to the no treatment TBI group and the cell‐only group. Insulin‐like growth factor‐1 known to have a crucial role in MSC proliferation and putative differentiation to neuronal cells .…”
Section: Cell Therapy In Tbimentioning
confidence: 99%
“…In recent years, several studies have investigated the potential neuroprotective effects of stem cells and their ability to stimulate endogenous regeneration in animal models of TBI (7)(8)(9)(10)(11). Although the functional mechanisms of this therapy have yet to be determined, these previous studies demonstrated that stem cell administration improves functional recovery following TBI in experimental animals.…”
Section: Introductionmentioning
confidence: 99%